Influence of Anodization Time on Photovoltaic Performance of DSSCs Based on TiO2 Nanotube Array. (28th November 2016) - Hu, Jinghua; Hu, Shiwu; Yang, Yingping; Tong, Shengqiang; Cheng, Jiejie; Chen, Mengwei; Zhao, Li; Duan, Jinxia
Abstract : Highly ordered TiO2 nanotube arrays (TNT arrays) were fabricated by two-step anodization process. In order to further improve the performance of DSSCs, TNT arrays were optimized by changing the anodization conditions to meet the requirements of high-performance photoanode. The photoelectric conversion properties of DSSCs based on P25/TNT arrays double-layer film with different anodization time were investigated and compared. The results show that the conversion efficiency of 4.20% was achieved in double-layer photoanode at 18 h, with an open-circuit voltage (V oc ) of 0.65 V and short-circuit current density (J sc ) of 9.98 mA cm −2 .